1996
DOI: 10.1111/j.1469-8137.1996.tb04516.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and spread of the endophyte Stagonospora pteridiicola in Pteridium aquilinum, other ferns and some flowering plants

Abstract: SUMM.^RYPteridium aquilinum (L.) Kuhn was sampled for colonization by Stagonospora pteridiicola in Great Britain, Hungary and Australia. British samples gave the highest incidence of f)8",, during September and 12"o at the beginning of the growing season. Hungarian samples showed a similar frequency. The fungus was not found in Australian bracken. Five field-collected fern species other than bracken did not contain the fungus in May when bracken already had a colonization frequency of \2"i, in the pinnules. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 10 publications
0
24
0
4
Order By: Relevance
“…Considered ubiquitous among terrestrial plants, fungal endophytes have been found in healthy tissues of all plant taxa sampled to date (e.g., Petrini et al 1982, Clay 1988, Legault et al 1989, Schulz et al 1993, Rodrigues 1996, Fisher 1996, Lodge et al 1996, Fröhlich and Hyde 1999 and in habitats ranging from coastal mangroves (Kumaresan andSuryanarayanan 2001, Okane et al 2001) to north-temperate evergreen forests (e.g., EspinosaGarcia andLangenheim 1990, Muller andHallaksela 1998), temperate pastures and grasslands (e.g., Clay andHolah 1999, Vinton et al 2001), semiarid regions of the southwestern U.S.A. (Faeth and Hammon 1997), and tropical forests (e.g., Rodrigues 1994, Arnold et al 2000, Cannon and Simmons 2002. Most studies have focused on clavicipitaceous fungi that inhabit temperate grasses (e.g., Clay 1991, Saikkonen et al 1998, Malinowski and Belesky 1999; in contrast, endophytic fungi associated with leaves of woody angiosperms, especially in tropical forests, are poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Considered ubiquitous among terrestrial plants, fungal endophytes have been found in healthy tissues of all plant taxa sampled to date (e.g., Petrini et al 1982, Clay 1988, Legault et al 1989, Schulz et al 1993, Rodrigues 1996, Fisher 1996, Lodge et al 1996, Fröhlich and Hyde 1999 and in habitats ranging from coastal mangroves (Kumaresan andSuryanarayanan 2001, Okane et al 2001) to north-temperate evergreen forests (e.g., EspinosaGarcia andLangenheim 1990, Muller andHallaksela 1998), temperate pastures and grasslands (e.g., Clay andHolah 1999, Vinton et al 2001), semiarid regions of the southwestern U.S.A. (Faeth and Hammon 1997), and tropical forests (e.g., Rodrigues 1994, Arnold et al 2000, Cannon and Simmons 2002. Most studies have focused on clavicipitaceous fungi that inhabit temperate grasses (e.g., Clay 1991, Saikkonen et al 1998, Malinowski and Belesky 1999; in contrast, endophytic fungi associated with leaves of woody angiosperms, especially in tropical forests, are poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these fungi can be cured of their EHB via antibiotic treatment, and both partners often can be cultivated in isolation on standard nutrient media (14,24,25). Much like their fungal hosts, most EHB of foliar endophytes appear to be horizontally transmitted (14,15,(24)(25)(26)(27)(28)(29), but the factors determining the dynamics of these associations are poorly understood.EHB of foliar endophytes can strongly influence fungal phenotypes, with consequences for plant-fungal interactions (24; K. R. Arendt, S. J. Araldi-Brondolo, D. A. Baltrus, and A. E. Arnold, unpublished data). Curing fungi of EHB provides one important tool for empirical assessment of the effects of these bacteria and has been used in a variety of studies (14,22,24,30).…”
mentioning
confidence: 99%
“…Moreover, these fungi can be cured of their EHB via antibiotic treatment, and both partners often can be cultivated in isolation on standard nutrient media (14,24,25). Much like their fungal hosts, most EHB of foliar endophytes appear to be horizontally transmitted (14,15,(24)(25)(26)(27)(28)(29), but the factors determining the dynamics of these associations are poorly understood.…”
mentioning
confidence: 99%
“…This black yeast-like fungus (meristematic fungus) is ubiquitous saprophyte of phyllosphere and other aerial plant parts (domsch, Gams and Anderson 1980). It is frequently noted as endophyte of different plants, among them in bark and xylem of Eucalyptus (bettucci et al 1999), leaf fern Pteridium aquilinum (Fisher 1996), twigs, leaves and buds of Acer pseudoplatanus and other trees (Pugh, buckley 1971). A. pullulans can be antagonistic against a number of phytopathogenic fungi (Andrews et al 1983).…”
Section: Methodsmentioning
confidence: 99%